2017
DOI: 10.1002/2017jd026467
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of albedo versus cloud fraction relationships in liquid water clouds using heuristic models and large eddy simulation

Abstract: The relationship between the albedo of a cloudy scene scriptA and cloud fraction fc is studied with the aid of heuristic models of stratocumulus and cumulus clouds. Existing work has shown that scene albedo increases monotonically with increasing cloud fraction but that the relationship varies from linear to superlinear. The reasons for these differences in functional dependence are traced to the relationship between cloud deepening and cloud widening. When clouds deepen with no significant increase in fc (e.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(53 citation statements)
references
References 54 publications
4
19
0
Order By: Relevance
“…This is also true for the fit slope of CSDs and the total area of large clouds (Figure ). The coherence between the time series of rain and CSDs lends credence to the idea that the similar frequencies in charge‐discharge cycles (Dagan et al, ) and CSD variability (Feingold et al, ) are indeed related. While the aforementioned papers identified a dominant frequency of 80 – 90 min for BOMEX simulations, the period of the precipitation cycle in our deeper cumulus simulations is not exactly captured with periods between 1 and 2 hr, and it is found that inclusion of low frequency modes is important.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…This is also true for the fit slope of CSDs and the total area of large clouds (Figure ). The coherence between the time series of rain and CSDs lends credence to the idea that the similar frequencies in charge‐discharge cycles (Dagan et al, ) and CSD variability (Feingold et al, ) are indeed related. While the aforementioned papers identified a dominant frequency of 80 – 90 min for BOMEX simulations, the period of the precipitation cycle in our deeper cumulus simulations is not exactly captured with periods between 1 and 2 hr, and it is found that inclusion of low frequency modes is important.…”
Section: Discussionmentioning
confidence: 54%
“…Time series analysis showed that the build‐up of cloud water leads that of rain water build‐up by approximately 20 min. For the same case, Feingold et al () found an oscillation in the fit slope of CSDs with similar periodicity (≈80 and ≈15 min). These results indicate a physically based link between the precipitation cycle and the cloud size distribution cycle.…”
Section: Resultsmentioning
confidence: 69%
“…Calculating average cloud albedo across the global oceans based on CERES data for cases where the ice cloud fraction is zero, following Bender et al (), yield a scaling factor of 0.3 to 0.5 for marine boundary‐layer clouds. The linear scaling is appropriate for stratocumulus clouds where clouds are capped by the inversion and therefore deepen relatively little as they widen (Feingold et al, ).…”
Section: Rapid Adjustments To Aerosol‐cloud Interactionsmentioning
confidence: 99%
“…The spatial organization in a cloud field can add to this stochastic variability by introducing pertur bations in the cloud populations on scales much larger than the boundary layer depth (e.g., Seifert and Heus 2013). Physical-dynamical processes that drive spatial organization include cold pool formation (e.g., Schlemmer and Hohenegger 2014) and oscillations (Sakradzija et al 2015;Feingold et al 2017).…”
Section: Introductionmentioning
confidence: 99%